Mild early course of osteogenesis imperfecta type XIV - a case report - Nikola Georgijev; Slobodan Gazikalović; Zoran Paunović; Nikola Ilić; Adrijan Sarajlija (Биомедицинска истраживања, 2022)
Introduction: Mutations in TMEM38B gene, which encodes the endoplasmatic reticulum membrane trimeric intracellular cation channel (TRIC) type B, cause osteogenesis imperfecta type XIV. So far there have been only four different pathogenic variants reported in TMEM38B. Clinical features of osteogenesis imperfecta type XIV described in scarce reports include osteopenia, femoral bowing, low trauma fractures, scoliosis, muscular hypotonia and cardiac pathology. Case report. A 2-month-old male infant was referred to a clinical geneticist office due to bone deformities. The shortening of the limbs was observed during the prenatal ultrasound examination in seventh month of pregnancy. Prenatal cytogenetic analysis was performed from a fetal blood sample and showed normal findings. Neither fetal fractures were observed prenatally, nor any occurred during vaginal labor. During the first clinical exam by the clinical geneticist, discrete rhizomelia and bluish sclerae were observed. Due to the suspicion of skeletal dysplasia, indication for genetic analysis was established. Next generation sequencing panel for skeletal dysplasia showed homozygous deletion of exons 1 and 2 in the TMEM38B gene, confirming osteogenesis imperfecta type XIV. At the follow-up visit performed at 12 months of age, no fractures were reported. Several skeletal deformities were observable: discrete frontal bossing, rhizomelic upper extremities, slightly bowed thighs and shins. The infant achieved normal psychomotor development. A radiographic examination showed bowing of long bones of the lower extremities, without significant osteopenia. Conclusion: Absence of early fractures is rare in osteogenesis imperfecta type XIV. Relatively mild clinical features of our patient therefore contribute to the understanding of the phenotype of osteogenesis imperfecta type XIV and its relation to the genotype.
Keywords: skeletal dysplasia; TMEM38B gene; deletion